CFD modeling of flammable refrigerant leaks inside machine rooms: Emergency ventilation rates for different size chillers. (14th September 2018) - Zhang, Shiling; Papas, Paul; Hu, Liangbo; Verma, Parmesh; Lord, Richard; Burns, Larry
Abstract : Computational fluid dynamics (CFD) simulations, verified against test data, were undertaken to quantify ventilation dilution requirements needed for mitigating flammability risks during leaks of mildly flammable refrigerants from different size chillers inside machine rooms in an extension of our prior work for very large chillers. For this study, a 376 m 3 machine room configuration was modeled using CFD to simulate significant refrigerant leaks from a chiller with different refrigerant charge levels. Three different mildly flammable refrigerants with various leak rates and various air ventilation rates were evaluated to understand dilution requirements to prevent significant refrigerant flammable mass accumulation. These results are discussed in light of previously published machine room ventilation requirements for mitigating sustained leaks from large chillers, and used to establish a generalized relationship for the emergency ventilation rate needed for mitigating risks for significant refrigerant leaks inside machine rooms for the full range of chiller charge levels incorporating any mildly flammable refrigerant with A2L safety group classification.